The PCNA-associated protein PARI negatively regulates homologous recombination via the inhibition of DNA repair synthesis - Burkovics, Peter; Dome, Lili; Juhasz, Szilvia; Altmannova, Veronika; Sebesta, Marek; Pacesa, Martin; Fugger, Kasper; Sorensen, Claus Storgaard; Lee, Marietta Y W T; Haracska, Lajos; Krejci, Lumir (Nucleic acids research, 2016)
Successful and accurate completion of the replication of damage-containing DNA requires mainly recombination and RAD18-dependent DNA damage tolerance pathways. RAD18 governs at least two distinct mechanisms: translesion synthesis (TLS) and template switching (TS)-dependent pathways. Whereas TS is mainly error-free, TLS can work in an error-prone manner and, as such, the regulation of these pathways requires tight control to prevent DNA errors and potentially oncogenic transformation and tumorigenesis. In humans, the PCNA-associated recombination inhibitor (PARI) protein has recently been shown to inhibit homologous recombination (HR) events. Here, we describe a biochemical mechanism in which PARI functions as an HR regulator after replication fork stalling and during double-strand break repair. In our reconstituted biochemical system, we show that PARI inhibits DNA repair synthesis during recombination events in a PCNA interaction-dependent way but independently of its UvrD-like helicase domain. In accordance, we demonstrate that PARI inhibits HR in vivo, and its knockdown suppresses the UV sensitivity of RAD18-depleted cells. Our data reveal a novel human regulatory mechanism that limits the extent of HR and represents a new potential target for anticancer therapy.
Keywords: HEK293 Cells; rekombinační oprava DNA; Ultraviolet Rays; DNA vazebné proteiny; DNA-Binding Proteins; Ubiquitin-Protein Ligases; Amino Acid Motifs; DNA Polymerase III; HEK293 buňky; ultrafialové záření; Humans; Recombinational DNA Repair; ubikvitinligasy; aminokyselinové motivy; DNA-polymerasa III; DNA; lidé